EKSTRAK ETANOL DAUN ALPUKAT (Persea americana Mill.) SEBAGAI PENURUN EDEMA GLOMERULUS DAN KERUSAKAN SEL GINJAL TIKUS PUTIH (Rattus norvegicus) - Indah Retuwati Ramadhana; Joko Waluyo; Kamalia Fikri (FKIP Universitas Jember, 2018)
Avocado leaves (Persea americana Mill.) historically used as a herbal medicine used to ease the expense of urine and crushed a kidney stone in the urinary tract. Avocado leaves contain sugar, d-parseit, quercetin, flavonoids, and compounds sterin. The availability of avocado leaves in the society becames a great opportunity to be utilized as a herbal medicine, it is unknown yet whether the avocado leaves extract was able to decrease edema glomerulus and cell damage in the kidneys. The aim of this research knew the effect of ethanol extract of avocado leaves to decrease edema glomerulus and cell damage kidney of white rat. The research method used The Post Test Only Control Group Design. The dose was 100 mg/0.2kg bw, 200 mg/0.2kg bw, 300 mg/0.2kg bw, with inducer (ethylene glycol + ammonium chloride) as positive control, the treatment carried out during 10 days. Data analysis used Anova. The results showed for parameter damage the glomerulus with (F = 4.931, p = 0.027, < 0.05) which means there was the effect of the ethanol extracts of avocado leaves significantly to decrease edema glomerulus, while parameters proximal tubule damage with (F = 5.755, p = 0.018, < 0.05) which means there was the effect of the ethanol extracts of avocado leaves significantly to decrease cell damage kidney white rat. The dose of ethanol extract of avocado leaves which are most effective against the decrease of edema glomerulus was 100 mg/0.2kg bw and cell damage kidney white rat was 200 mg/0.2kg bw.